Acute and subacute toxicity of virgin coconut oil in rodents - Pekson, Ryan C.
The heightened commercial interest on the possible therapeutic effects of virgin coconut oit (VCO) has propelled a number of studies in humans in both the adult and pediatric populations. Adequate review of literature, however, failed to show any on the toxicity profile of VCO. OBJECTIVE: This research is designed to determine the acute and subacute toxicity of oral administration of virgin coconut oil in Swiss-Webster mice and Sprague-Dawley rats, respectively, to generate data that can be extrapolated for long-term animal and clinical studies. METHODOLOGY: The procedures for the oral acute and subacute toxicity studies were adopted from the established protocols of the Organization for Economic Co-operation and Development (OECD). In the acute toxicity study, fifty (50) adult Swiss-Webster mice were divided into five groups consisting of ten animals (5 males and 5 females) and were allocated by block randomization into four VCO treatment groups (36.7 g/Kg, 5.8 g/Kg and 2.3 g/Kg) and the control (normal saline solution at 40.7 g/Kg). Observations were made for 8 hours after gavage administration and daily thereafter for 14 days using the Irwin's multidimensional observation sheet. In the subacute toxicity study, forty eight (48) Sprague-Dawley rats (10-12 weeks old) were allocated by block randomization into four (4) groups, three (3) of which received VCO (6.3 g/Kg) (high dose), 4.14 g/Kg (medium) and 2.7 g/Kg (low) by gavage tube feeding for 21 days, and one group served as control (normal saline solution, 7 g/Kg). These rats were observed for toxidromes with analyses of hematologic, blood chemistry, urine and fecal parameters. Gross pathologic examination was performed and a detailed histopathologic examination of the liver, heart, kidney, lungs, spleen, thymus, thorasic aorta, and other organs with suspected abnormality were done on Day 10 and Day 21. RESULTS: The median lethal dose (LD50) of VCO was not established but was determined to be greater than 36.7 g/Kg in mice. The oral no adverse effect level (NOAEL) in mice was determined at 2.3 g/Kg. Acute toxidrome included the presence of oily mucoid stool and blood-streaked feces which resolved in 24 hours. Subacute toxicity studies in rats showed a dose- dependent reduction in feed consumption which resulted in decrease in body weight of the animals. Fasting blood sugar (FBS) significantly decreased at 2.7 g/Kg and 4.14 g/Kg but relatively increased at 6.7 g/Kg of VCO. Significant increases in serum triglycerides, blood urea nitrogen (BUN), creatinine, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were observed to be directly proportional to the dose. There were no treatment-related changes in hematological, stool, and urinary parameters. Histopathological examinations revealed significant hepatic and renal lesions in rats given 4.14 g/Kg and 6.3 g/Kg of VCO. CONCLUSIONS: The LD50 of VCO was determined to be greater than 36.7 g/Kg in mice with the no adverse effect level (NOAEL) at 2.3 g/Kg. Reversible acute toxidrome consisted of oily stool and blood-streaked feces. Subacute administration of VCO was associated with dose-dependent elevation of serum trigycerides, blood urea nitrogen, creatinine, AST, and ALT. Fasting blood sugar was reduced at low to medium doses of VCO, while an increase in FBS was observed at high dose (6.3 g/Kg). VCO was potentially hepatotoxic and nephrotoxic at medium (4.14 g/Kg) and high doses (6.3 g/kg) in rats.